A leitura freudiana de Norbert Elias sobre o nazismo: civilização como produtora de anticivilização - Braga, Sabrina Costa (2018)
The comparisons between the ideas of Norbert Elias and Sigmund Freud have been the subject of several studies that stablish that there is a connection in the way both authors understand human societies. In accordance with the studies about the civilizatory process, Elias devoted himself to the search of explanations of how, within a civilized society like the one in 20th Century Germany, the existence of concentration camps was made possible. Our goal here is to beyond pointing out the presence of psychoanalysis in Elias theory of the Civilizatory process, to also show how psychoanalysis is present in its interpretation of the Nazi phenomenon. In order to reach such goal, we start from a detailed investigation of Elias’s work, from his approach to the historical and cultural context in which he lived and the conditions in which his writings were produced. Then moving on to a detailed study of the main aspects of his analysis of Nazism, until we come to the role of psychoanalysis as a possible axis for understanding the Elisian theory.